Guida per la valorizzazione della multifunzionalità dell'agricoltura - Leonardo, Casini (Proceedings e report, 2009)
This book publishes the results of the inter-regional project on "Evolutionary dynamics of agricultural enterprises and multifunctionality". Starting from the identification of a shared theoretical framework of the concept of multifunctionality, the study has developed a method for zoning the territory aimed at defining the different roles played by agriculture. The development of case studies, and meetings with stakeholders and focus groups, have made it possible to identify the weak and strong points within and outside the enterprises, with particular reference to the multifunctional components and the degree of repeatability and transferability of the experiences analysed. The result is to bring to light needs in terms of policies, tools for the valorisation of multifunctionality and strategies that enable the agricultural enterprises to commercially valorise functions not traditionally pertinent to the market.